2007
DOI: 10.1186/1753-6561-1-s1-s76
|View full text |Cite
|
Sign up to set email alerts
|

Application of structural equation models to construct genetic networks using differentially expressed genes and single-nucleotide polymorphisms

Abstract: Understanding the genetic basis of human variation is an important goal of biomedical research. In this study, we used structural equation models (SEMs) to construct genetic networks to model how specific single-nucleotide polymorphisms (SNPs) from two genes known to cause acute myeloid leukemia (AML) by somatic mutation, runt-related transcription factor 1 (RUNX1) and ets variant gene 6 (ETV6), affect expression levels of other genes and how RUNX1 and ETV6 are related to each other. The SEM approach allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Finally, tackling a completely different problem, Lee et al [2007] proposed using SEMs to help understand relationships in expression data. Although their models included only latent genetic factors controlling the expression of 12 genes, environmental factors could have been included, had they been available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, tackling a completely different problem, Lee et al [2007] proposed using SEMs to help understand relationships in expression data. Although their models included only latent genetic factors controlling the expression of 12 genes, environmental factors could have been included, had they been available.…”
Section: Discussionmentioning
confidence: 99%
“…Structural equation models. Lee et al [2007] found that the optimal model involved correlation but not causation between the latent variables (representing RUNX1 and ETV6). Nor was there evidence for an additional latent variable controlling both RUNX1 and ETV6.…”
Section: Data Modelingmentioning
confidence: 97%
See 1 more Smart Citation
“…SEM has been successfully used to elucidate causal relationships in disparate fields such as econometrics, sociology and psychology 7–9. In addition, it has been applied to Quantify Trait Loci (QTLs) for association and linkage mapping in biology,10,11 as well as to identify genetic networks from microarray data or SNP data 1214. The significant features of SEM are the inclusion of latent variables into the constructed model and the ability to infer the network, including the cycle structure.…”
Section: Introductionmentioning
confidence: 99%
“…7–9 In addition, it has been applied to Quantify Trait Loci (QTLs) for association and linkage mapping in biology, 10,11 as well as to identify genetic networks from microarray data or SNP data. 1214 The significant features of SEM are the inclusion of latent variables into the constructed model and the ability to infer the network, including the cycle structure. Additionally, the linear relationships between the latent variables and the observed variables are assumed to minimize the differences between the fitted covariance matrix and the calculated sample covariance matrix.…”
Section: Introductionmentioning
confidence: 99%